2017
DOI: 10.1200/jco.2017.35.15_suppl.5571
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the repertoire of immune checkpoint markers expressed on peripheral and ascites CD8+ T cells in ovarian cancer.

Abstract: 5571 Background: Understanding the immune checkpoint marker repertoire can facilitate development of therapeutic strategies to improve efficacy of immune-based therapies. We used a novel high-dimensional flow cytometry panel to determine co-expression patterns of immune checkpoint markers and effector function of CD8+ T cells from peripheral blood and ascites of patients newly diagnosed with ovarian cancer. Methods: Peripheral blood and ascites samples were collected from patients with epithelial ovarian canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Costimulatory receptors on T cells further activate the T cells and amplify the immune response whereas checkpoint receptors inhibit the T cells and dampen the response. Tumor microenvironment (TME) is enriched with mediators of immunosuppression, which induce the expression of checkpoint receptors on the surface of T cells and promote a dysfunctional/exhausted phenotype in T cells, which is briefly described in the following section [59][60][61][62][63][64][65].…”
Section: T-cell Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Costimulatory receptors on T cells further activate the T cells and amplify the immune response whereas checkpoint receptors inhibit the T cells and dampen the response. Tumor microenvironment (TME) is enriched with mediators of immunosuppression, which induce the expression of checkpoint receptors on the surface of T cells and promote a dysfunctional/exhausted phenotype in T cells, which is briefly described in the following section [59][60][61][62][63][64][65].…”
Section: T-cell Activationmentioning
confidence: 99%
“…Progressive loss of T-cell effector functions, termed 'T-cell exhaustion' is commonly seen during chronic viral infections and in cancer. The significance of T-cell exhaustion in cancer has rapidly gained importance and several studies have identified the presence of 'exhausted' T cells in TME [59][60][61][62][63][64][65].…”
Section: T-cell Exhaustionmentioning
confidence: 99%